La concesión de los ferrocarriles en el Perú en el periodo 1826-1879 - Retamozo Linares, Alberto (Universidad ESAN, 2024)
In 19th century, the construction of railroads in Peru was associated with pro gress and general welfare, driven by the exploitation of guano and the parti cipation of the private sector through concessions. However, this process was marked by disorderly spending, lack of planning and control, and unlawful conduct. When Manuel Pardo assumed the presidency in 1872, he found that the railroad policy had been a failure, leaving the Treasury without resources. In spite of this, subsequent governments continued with this policy, enacting laws, carrying out studies and granting concessions to contractors such as Enrique Meiggs. The way in which the concessions were handled, the benefits for the proponents and the corrupt behavior led to the failure of the railroad project and the national decline. In short, the idea of progress through the railroads was frustrated by the lack of planning, financial disorder and co rruption in the railroad construction process.

En el siglo XIX, la construcción de ferrocarriles en Perú se asoció al progreso y al bienestar general, impulsada por la explotación del guano y la partici pación del sector privado a través de concesiones. Sin embargo, este proceso estuvo marcado por un gasto desordenado, la falta de planificación y control, y conductas contrarias a la legalidad. Cuando Manuel Pardo asumió la pre sidencia en 1872, constató que la política ferrocarrilera había sido un fracaso, dejando a la Hacienda Pública sin recursos. A pesar de ello, los gobiernos posteriores continuaron con esta política, promulgando leyes, haciendo estu dios y otorgando concesiones a contratistas como Enrique Meiggs. La forma en que se manejaron las concesiones, los beneficios para los proponentes y las conductas corruptas llevaron al fracaso del proyecto ferrocarrilero y contribu yeron al ocaso nacional. En resumen, la idea del progreso a través de los ferro carriles se vio frustrada por la falta de planificación, el desorden financiero y la corrupción en el proceso de construcción de las vías férreas.
Keywords: Concessions; Transportation infrastructure; Concesiones; History of peruvian law; Infraestructura de transporte; Historia del derecho peruano; Public investment; Inversión pública; https://purl.org/pe-repo/ocde/ford#5.05.01